ACEHNESE UNDERGRADUATE STUDENTS’ STRATEGIES IN PREPARING FOR TOEFL PREDICTION: A PRELIMINARY STUDY - Ayuna Netta; Ika Kana Trisnawati (Universitas Islam Negeri Banda Aceh, 2019)
This study focused on the strategies of undergraduate students in preparing for the TOEFL Prediction. The study distributed questionnaires to the students of Universitas Muhammadiyah Aceh, gathering a sample of 15 students of different majors. The findings revealed that the students’ most used strategy was self-study, involving learning with various English materials. This study suggests that future research focus on the reasons influencing test-takers’ decision in test preparation strategies.